Analysing the importance of glyphosate as part of agricultural srategies: A discrete choice experiment - Michael Danne; Oliver Mußhoff; Michael Schulte (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2018)
The use of glyphosate plays an important role in farmers' strategic decisions for reducing weed pressure and yield losses. In this paper, the use of glyphosate is analysed as part of a complete agronomic strategy in which the farmer has to choose between the use of a combination of mechanical and chemical weed control. A special aim was to analyse the trade-off in the farmers' preferences between a cultivation strategy with or without glyphosate. The empirical analysis is based on a discrete choice experiment with 328 German farmers. It was found that after the harvest of rapeseed, farmers have a preference for mulch seeding with glyphosate rather than without it. The preference for glyphosate use is affected by the weed pressure and the presence of specific weeds. While the farmers' risk attitude has no influence on the decision to use glyphosate, we observed an increasing preference for its use on larger farms. Furthermore, our results reveal that farmers prefer mechanical weed control in pre-sowing instead of the use of selective herbicides in pre- or post-emergence. This preference increases if weed resistance is an issue on the farm. Potential yield impacts caused by glyphosate use show that yield losses have a higher impact on the farmers' decision than yield gains. We conclude that farmers prefer the use of glyphosate to other alternatives as it is an im-portant part of their agronomic strategy to prevent weed infestation and save work and labour costs, especially on large farms.
Keywords: 330; glyphosate; mulch seeding; rapeseed; agronomic strategy; discrete choice experiment; farmer's preference